Implementation of Developing English Learning Methods Through Audio Visual Technology for Student of Elementary School in Bangkalan Subdistrict - Ramadlani, Anny Shobichah; Fikri, Dzul (Universitas Cokroaminoto Palopo, 2023)
The primary goal of this research is to create educational videos with both auditory and visual elements to improve the overall learning experience, focusing on English lessons for 3rd-grade elementary students. By utilizing learning media, the teaching and learning process becomes easier and more engaging, enabling students to grasp the subject matter effortlessly. Additionally, it enhances learning efficiency as it aligns with the predetermined learning objectives. This research follows the Research and Development (R&D) methodology with the ADDIE model development framework. Based on the questionnaire results, a score of 80% was obtained, leading to the conclusion that this audio-visual media is 'very good' for enhancing the quality of English education in the Student of Elementary School in Bangkalan Subdistrict.